Spirituality in pediatric practice - Garanito, Marlene Pereira (2016)
The theme of palliative care in pediatric practice represents a relevant topic for discussion in the context of bioethics. In this respect, we seek to emphasize that the spiritual dimension is an integral part of the care of pediatric patients, and therefore health teams need to be able to embrace this transcendent movement and be attentive to the spiritual needs of pediatric patients, as well as their caregivers.